Market reactions to dividends announcements: evidence from the Warsaw Stock Exchange - Michał Gnap (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2022)
The main goal of article is to investigate the Warsaw Stock Exchange market reaction to announcements in connection with planned dividend payouts. The research sample comprises 45 entities listed on the Warsaw Stock Exchange between 2017 and 2021. The analysis uses the simple rate of return and the buy-and-hold excess return. Regression analysis shows that change in DPR does not fully explain the share price changes. Nonetheless, the weak market reaction to dividend payment announcements may lead to the conclusion that Polish stocks already take into account information about dividend payouts.